(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
This study focuses on clinical trials in Africa and suggests that a human rights-based and biolegal approach is a viable solution for ensuring effective protection and for promoting the freedom of research, ethical experimentation and the equitable enjoyment of the benefits of scientific progress, and for ensuring availability and accessibility of drugs at fair conditions. International cooperation within the African Union and the NEPAD Agency is advanced as the appropriate framework for debate and mediation between divergent positions, by relying on helpful international instruments and promoting justiciability, especially through the African Court on Human and Peoples’ Rights.